A high-static-low-dynamics stiffness vibration isolator via an elliptical ring. (1st January 2022) - Han, Wen-Ju; Lu, Ze-Qi; Niu, Mu-Qing; Chen, Li-Qun
Highlights: The force-displacement relation is established for a compressed elliptical ring. The elliptical ring isolator exhibits high-static-low-dynamic stiffness. The isolator achieves the minimum resonance frequency with an optimal eccentricity. Abstract: An elliptical ring is used to implement a novel type of high-static-low-dynamic vibration isolation. Under the compression deformation, the elliptical ring produces a nonlinear restoring force due to the coupling of the tension and the curvature caused by the stretching. For the elliptical ring under a uniaxial pressure, its force-displacement relation is derived from the Euler–Bernoulli beam theory. The force-displacement relation is experimentally validated via a digital force gauge. The dynamic equation is established for the elliptical ring isolator under a harmonic base excitation. It is revealed that the elliptical ring isolator is with high-static-low-dynamic stiffness. The harmonic balance method is applied to determine approximately steady-state responses of the vibration isolator, and thus the displacement transmissibility of the isolator can be analytically predicted. The analytical results show the effects of the eccentricity. The analytical outcomes are numerically confirmed by the direct integration of the dynamic equation. Under certain conditions, there is an optimal eccentricity for the fixed elliptical circumference, and the displacement transmissibility achieves a minimum value at the optimal eccentricity. The elliptical ring isolator is experimentally tested, and the experimental results validate the analytical outcomes.